Contrasting effects of fire frequency on plant traits of three dominant perennial herbs from Chaco Serrano. (24th May 2016) - Carbone, Lucas M.; Aguilar, Ramiro
Abstract: Fire frequencies are currently increasing in many regions across the world as a result of anthropic activities, affecting ecological processes and plant population dynamics. Fire can generate important changes in soil properties, altering nutrient dynamics and thereby plant growth. Here we analyse fire frequency effects on soil quality and plant traits of three native perennial herbaceous plants ( Cologania broussonetii, Desmodium uncinatum and Rhynchosia edulis ; Fabaceae) with the capacity for biological N2 fixation that resprouts and are abundant after fire in Chaco Serrano forests. Based on 22‐year fire history, we assessed plant traits in sites with low and high fire frequencies along with unburned scenarios. We found significantly lower water content, nitrates and electrical conductivity in frequently burned soils. As a result, the three species showed consistently lower leaf area and specific leaf area in both fire frequencies, implying lower growth rates in comparison to unburned sites. However, total leaf biomass was not affected by fire, leaf phosphorus concentration was higher in R . edulis in high fire frequency and leaf N concentration was twice as large in plants growing in sites of high fire frequency in C . broussonetii and R . edulis . Such an increase in N and phosphorus concentrations is likely a result of both their conservative use of resources and their biological N2 fixation capacity. To our knowledge, this is the first record of such contrasting fire effects observed consistently in three co‐occurring species: while plant growth decreased with fire frequency, leaf nutritional traits remain unchanged or increased in frequently burned sites. Quality‐depleted and drier soils that result from increased fire frequencies may not only affect trait variation at the intraspecific level but can also drive to a homogenization of the plant community, selecting species with particular combinations of morphological and functional traits.